Talent development in Paralympic sport: Researcher and practitioner perspectives (Routledge, 2022)
Identifying and developing talented athletes to their fullest potential is a central concern of sports scientists, sports coaches, and sports policymakers. However, there is very little practical and theoretical knowledge for those working in Paralympic sport. The book collates the state of the science of current knowledge and practice in talent identification and development in this context by capturing international perspectives of current systems and processes.